2014
DOI: 10.1111/1469-0691.12740
|View full text |Cite
|
Sign up to set email alerts
|

Predicting pneumococcal community-acquired pneumonia in the emergency department

Abstract: The aim of this study was to quantify the value of clinical predictors available in the emergency department (ED) in predicting Streptococcus pneumoniae as the cause of community-acquired pneumonia (CAP). A prospective, observational, cohort study of patients with CAP presenting in the ED was performed. Pneumococcal aetiology of CAP was based on either bacteraemia, or S. pneumoniae being cultured from sputum, or urinary immunochromatographic assay positivity, or positivity of a novel serotype-specific urinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
4
1
Order By: Relevance
“…The prevalence of pneumococcal urinary antigen detection in our study (4.2%) was lower than reported in some prior CAP studies [13][14][15]21]. Reasons for lower pneumococcal prevalence in the current study may be multifactorial, including patient enrollment after the introduction of widespread pneumococcal conjugate vaccine use; inclusion of patients with all-cause CAP, including those with no pathogen detected; and systematic urinary antigen testing in the study population that did not rely on a clinician's decision to obtain the test.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…The prevalence of pneumococcal urinary antigen detection in our study (4.2%) was lower than reported in some prior CAP studies [13][14][15]21]. Reasons for lower pneumococcal prevalence in the current study may be multifactorial, including patient enrollment after the introduction of widespread pneumococcal conjugate vaccine use; inclusion of patients with all-cause CAP, including those with no pathogen detected; and systematic urinary antigen testing in the study population that did not rely on a clinician's decision to obtain the test.…”
Section: Discussioncontrasting
confidence: 88%
“…Most prior work suggests pneumococcal pneumonia cannot be accurately identified based on clinical features, because its presentation overlaps substantially with pneumonia of other etiologies [13]. Our study supports the notion that pneumococcal pneumonia cannot be prospectively identified based on clinical features alone.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…As a consequence misdiagnosis is common, and as clinical criteria alone are not predictive in identifying the causative organism [44] most patients are treated with broad-spectrum antibiotics that may encourage the spread of antibiotic resistance. The BinaxNOW urine antigen test (Alere, Waltham, Massachusetts, USA) is a rapid diagnostic test for S. pneumoniae infections that is routinely available in many hospitals.…”
Section: Diagnosticsmentioning
confidence: 99%